Home support workers perceptions of family members of their older clients: a qualitative study - Sims-Gould, Joanie (BMC Geriatr, 2015)
BACKGROUND: Health care discourse is replete with references to building partnerships between formal and informal care systems of support, particularly in community and home based health care. Little work has been done to examine the relationship between home health care workers and family caregivers of older clients. The purpose of this study is to examine home support workers’ (HSWs) perceptions of their interactions with their clients’ family members. The goal of this research is to improve client care and better connect formal and informal care systems. METHODS: A qualitative study, using in-depth interviews was conducted with 118 home support workers in British Columbia, Canada. Framework analysis was used and a number of strategies were employed to ensure rigor including: memo writing and analysis meetings. Interviews were transcribed verbatim and sent to a professional transcription agency. Nvivo 10 software was used to manage the data. RESULTS: Interactions between HSWs and family members are characterized in terms both of complementary labour (family members providing informational and instrumental support to HSWs), and disrupted labour (family members creating emotion work and additional instrumental work for HSWs). Two factors, the care plan and empathic awareness, further impact the relationship between HSWs and family caregivers. CONCLUSIONS: HSWs and family members work to support one another instrumentally and emotionally through interdependent interactions and empathic awareness. Organizational Care Plans that are too rigid or limited in their scope are key factors constraining interactions.